2015
DOI: 10.1016/j.jad.2015.03.048
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of poor sleep quality on mood outcome differs between men and women: A longitudinal study of bipolar disorder

Abstract: Background Sleep disturbance is bi-directionally related to mood de-stabilization in bipolar disorder (BD), and sleep quality differs in men and women. We aimed to determine whether perception of poor sleep quality would have a different effect on mood outcome in men versus women. Methods We assessed association between sleep quality (Pittsburgh Sleep Quality Index (PSQI)) at study intake and mood outcome over 2 years in subjects from the Prechter Longitudinal Study of Bipolar Disorder (N=216; 29.6% males). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 54 publications
4
26
0
Order By: Relevance
“…Findings extend previous studies showing sleep variability is associated with mood symptoms (Gruber et al, 2011; Saunders et al, 2015). However, while we found overall variability in sleep duration was associated with more negative and less positive affect ratings, day-to-day atypicality relative to one's average sleep duration was not associated with day-to-day affect ratings.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Findings extend previous studies showing sleep variability is associated with mood symptoms (Gruber et al, 2011; Saunders et al, 2015). However, while we found overall variability in sleep duration was associated with more negative and less positive affect ratings, day-to-day atypicality relative to one's average sleep duration was not associated with day-to-day affect ratings.…”
Section: Discussionsupporting
confidence: 89%
“…Sleep duration and variability has typically been evaluated with cross-sectional surveys (Goossens et al, 2010), and longitudinal studies with time points spaced months, or even years, apart (Gruber et al, 2011; Perlman et al, 2006; Saunders et al, 2015). Studies have employed actigraphy to measure sleep in bipolar patients, but sleep duration in these studies was only measured for one or two weeks (Harvey et al, 2005; Jones et al, 2005; Millar et al, 2004) and concurrent mood ratings were collected at one time point (Harvey et al, 2005; Jones et al, 2005) or by daily mood diary entries (Gershon et al, 2012; Millar et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Only duration of sleep was comparable in all analyzed groups. Our results are consistent with those presented by Wang and others (2014) and Geoffroy and colegues (2014) for BPD patients, as well as with the results presented by Saunders and others (2015) for UPD patients , Saunders et al 2015.…”
Section: Sleep Variablessupporting
confidence: 94%
“…Impaired sleep is partly associated with depression and anxiety disorders affecting females more frequently than males. A US longitudinal study also confirmed lower sleep quality in females than males, with poor sleep being a significant predictor of low mood (Saunders et al, 2015). Lower sleep quality in females with rheumatoid arthritis proved Czech study (Kaas, Tóthová, 2015).…”
Section: Discussionmentioning
confidence: 80%